Clinical Characteristics and Management of Late Urinary Symptom Flare Following Stereotactic Body Radiation Therapy for Prostate Cancer - Woo, Jennifer A.; Chen, Leonard N.; Bhagat, Aditi; Oermann, Eric K.; Kim, Joy S.; Moures, Rudy; Yung, Thomas; Lei, Siyuan; Collins, Brian T.; Kumar, Deepak; Suy, Simeng; Dritschilo, Anatoly; et al. (Frontiers in Oncology, 2014)
Purpose: Stereotactic body radiotherapy (SBRT) is increasingly utilized as primary treatment for localized prostate cancer (PCa). The late GU toxicity of SBRT has not been fully described. We characterize the clinical features of late urinary symptom flare (LUSF) and recommend conservative management approaches. Methods: Between Feb.08-Aug.11, 216 men with PCa were treated definitively with SBRT at GUH. Treatment was delivered using the CyberKnife (35 Gy-36.25 Gy in 5 fractions). The prevalence of CTC-graded toxicities and medication usage were assessed at each follow-up visit. Patient-reported symptoms were assessed using the AUA symptom score and the EPIC-26 at 1, 3, 6, 9, 12, 18 and 24 months. LUSF was defined as an increase in the AUA score of ≥ 5 points above baseline with a degree of severity in the moderate to severe range. The relationship between the occurrence of flare and pretreatment characteristics were examined. Results: Of the 216 patients, 29 (13.4%) experienced a late transient increase in the AUA score that met the criteria for LUSF. Among flare patients, median age was 66 yrs compared to 70 for those without flare (p = 0.007). In patients who experienced flare, CTC toxicities peaked at 9-18 months, and alpha-antagonist utilization peaked at 18 months (85%) before decreasing at 24 months. The EPIC urinary summary score of flare patients transiently declined between 6 months and 18 months before returning to baseline at two years post-SBRT. Clinically significant increases in frequency, weak stream and dysuria were seen at 12 months post-SBRT. Among flare patients, 42.9% felt that urination was a moderate to big problem at 12 months following SBRT. Conclusions: In this study, we characterize LUSF following SBRT. LUSF is a constellation of symptoms including frequency/urgency, weak stream and dysuria that transiently occurs 6-18 months post-SBRT. The maintenance of prophylactic alpha-antagonists may limit the bother associated with this syndrome.